Body fat distribution reference standards in Spanish adolescents: the AVENA Study - Moreno, L.A; Mesana, M.I; González-Gross, M; Gil, M; Ortega, F.B; Fleta, J; Warnberg, J; Leon, J.F; Marcos, A; Bueno, M (INTERNATIONAL JOURNAL OF OBESITY, 2007)
Objective: To present body fat patterning reference standards to identify children with a predominant distribution of body fat in the abdominal or truncal region of the body. Design: Cross-sectional study in a representative sample of Spanish adolescents aged 13–18 years. Subjects: A total of 2160 adolescents with a complete set of anthropometric measurements (1109 males and 1051 females). Measurements: Weight, height, body mass index, skinfold thickness (biceps, triceps, subscapular, suprailiac, thigh, calf) and waist and hip circumferences. Results: In the majority of the age groups, subscapular/triceps skinfolds ratio, trunk-to-total skinfolds percent (TTS%)and waist circumference values were significantly higher in males than in females; hip circumference was higher in females than in males, except at 15.5 years. In males, age showed a significant effect for all the body fat distribution indices; however, in females, the effect was only significant for triceps skinfold, waist and hip circumferences and waist-to-hip ratio. Smoothed age- and sex-specific triceps skinfold, subscapular skinfold, subscapular/triceps skinfolds ratio, TTS%, waist circumference and hip circumference, waist-to-hip and waist-to-height ratio percentile values for male and female adolescents have been established. Conclusion: These reference data for waist circumference and the other fat patterning indices, together with data from other countries, will help to establish international central obesity criteria for adolescents. The presented percentile values will give the possibility to estimate the proportion of adolescents with high or low regional adiposity amounts.